2021
DOI: 10.1136/bmjdrc-2021-002524
|View full text |Cite
|
Sign up to set email alerts
|

Time to start addressing (and not just describing) the social determinants of diabetes: results from the NEXT-D 2.0 network

Abstract: Time to start addressing (and not just describing) the social determinants of diabetes: results from the NEXT-D 2.0 network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Intersectoral educational cooperation for diabetes : Researchers said that intersectoral collaborative action is a beneficial and cost-effective strategy in improving health literacy, and multilevel, comprehensive literacy health interventions are increasingly used to prevent T2D. [ 23 48 49 50 51 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Intersectoral educational cooperation for diabetes : Researchers said that intersectoral collaborative action is a beneficial and cost-effective strategy in improving health literacy, and multilevel, comprehensive literacy health interventions are increasingly used to prevent T2D. [ 23 48 49 50 51 52 ]…”
Section: Resultsmentioning
confidence: 99%
“…Improved quality of life, fewer emergency visits, hospitalizations decreased costs, and subtle improvements in glycemic control have all been reported as benefits of utilizing home-based or integrated health unit delivery systems for diabetes management. However, a study that used a standard, all-condition CHW intervention and found subtle improvements in diabetes consequences, as well as other health benefits, found that most CHW interventions for adult diabetic populations were diabetes-centered and used structured curricula [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…The World Health Organization defines SDOH as the "complex, integrated, and overlapping social structures and economic systems (e.g., the social environment, physical environment, health services, and structural and societal factors) that are responsible for most health inequities (disparities) around the world" [37]. In NEXT-D2, the research teams began to advance the knowledge base of how rigorously evaluated population-based programs or policy changes can influence disparities in T2D prevalence and diabetes outcomes [38], and NEXT-D3 aims to continue this in a more explicit and focused way, with some projects directly intervening on SDOH. A NEXT-D3 subcommittee, comprised of representatives from each study site, is also working to develop a set of standardized and validated SDOH measures that can be used across the network.…”
Section: Next-d3 Conceptual Frameworkmentioning
confidence: 99%